The Islamic State: a clash within the Muslim ciilization for the new Caliphate - Marsili, M. (Studies in Conflict and Terrorism, 2016)
This study analyzes the political reasons that allowed the Islamic State to expand successfully in Syria and Iraq, by enabling to “franchise” worldwide, and the role of the regional governments in this issue. The article provides a different explanation from the classic approach of the “clash of civilizations” theorized by Samuel P. Huntington, ascribing responsibility for the growth and expansion of the Islamic State to the complex framework of geopolitical alliances within the Muslim civilization and the Arab world. The article highlights the attempt by Turkey to establish itself as a regional power and guidance of the Islamic world, by resurrecting the Caliphate, and, based on this, explains the contrast with the Islamic State, whose goal is the foundation of a globalized Caliphate. The plans of the Turkish President Erdogan for a Great Turkey, allied with Egypt, have foundered with the coup that ousted the Muslim Brotherhood from power. The study relates the connection of Ankara with the Kurds, regarding the management of the crisis in Syria and Iraq, and the Turkish liaison with regional powers (Iran, Egypt, Saudi Arabia, and Israel) and other powers (Russia, China, and the United States).